Relationship between physiological and biomechanical variables with aerobic power output in cycling - Lanferdini, F. J.; Bini, R. R.; dos Santos Cunha, G.; Lopes, A. L.; de Souza Castro, F. A.; Reischak de Oliveira, A.; Vaz , M. A. (Journal of Science and Cycling, 2014)
Performance in cycling may be determined by physiological and biomechanical parameters. The aim of this study was to assess the relationship between biomechanical and physiological variables with aerobic power output in cycling. Twelve cyclists and twelve non-athletes performed an incremental cycling test to exhaustion during their first evaluation session and a constant load cycling test in a second evaluation session. Aerobic power output and oxygen uptake were measured during the first evaluation session, while muscle volume (determined using ultrasound measures in static conditions) and pedal forces were measured at the second session. Pedal forces were used to compute total force applied to the pedal and force effectiveness. Two multivariate stepwise regression analyses were conducted to measure the relationship between power output and oxygen uptake obtained at the second ventilatory threshold (VT2), muscle volume, total force applied to the pedal, force effectiveness and lower limb muscle activation for cyclists and non-athletes. Only oxygen uptake at the VT2 was significantly related to power output for non-athletes ( ) (r = 0.64, p = 0.03), whereas the resultant force was included in the regression model for cyclists (r = 0.66, p = 0.02). Muscle volume, pedal force effectiveness and muscle activation seem to have a minor effect in aerobic power output during cycling.